Investigation of reducing electricity consumption in the refrigerator by using domestic refrigerant MC-22. Issue 4 (April 2020) - Mutaufiq, M; Berman, E T; Sumardi, K; Wiyono, A; Gandidi, I M
Abstract: A household refrigerator was machine that operates continuously throughout the day to keep food fresh. So that a little savings in electricity consumption was very beneficial. The purpose of this study was to obtain savings in refrigerator electricity consumption by replacing R-134a working fluid with Musicool-22 (MC-22) as natural refrigerant. Furthermore, to reducing global warming potential of the earth's surface due to HFCs refrigerants. The study was designed experimentally with the retrofit refrigerant drop in substitute method on refrigerator. The test was started by measuring the performance of refrigerators using R-134a working fluid. Then the working fluid R-134a was retrofitted with MC-22 with a mass of 15%, 20%, 25%, 35%, 45%, and 65% of the mass of R-134a. Finally, the performance of the refrigerator that has been retrofitted using the MC-22 was measured as a measurement of the performance of the refrigerator using the R-134a. The test results showed that, when the refrigerator was retrofitted using MC-22 with a mass of refrigerant 25% mass of R-134a refrigerant, the performance of the refrigerator increases. Electricity consumption was more efficient with a marked decrease in electrical power requirements to 12.2%. In addition, the freezer room temperature is lower at 6.9 °C compared to when operating with R-134a working fluid.